Tanzania : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
This paper summarizes the Joint Staff Assessment (JSA) on the Poverty Reduction Strategy Paper (PRSP) of Tanzania. It analyzes the second Poverty Reduction Strategy Progress Report, and confirms that Tanzania continues to make significant progress both in terms of implementation of the country's Poverty Reduction Strategy (PRS) and in refining the strategy. Based on this PRSP Progress Report, the staffs of the World Bank and the IMF consider that Tanzania's poverty reduction strategy remains a sound basis for Bank and IMF concessional assistance.